Immune and growth response of indigenous pedi goats vaccinated with blanthrax to an inclusion of Moringa oleifera (Drumstick Tree) in Cenchrus ciliaris (Buffel Grass) hay-based diet - Gumede, Lungile; Tyasi, Thobela L.; Chitura, Teedzai; Mbatha, Khanyisile R. (Advances in Animal and Veterinary Sciences, 2022)
The study aimed to ascertain the immunomodulatory effects of Moringa oleifera (M. oleifera) leaves supplemented to the diets of wether BaPedi goats following vaccination with blanthrax vaccine. Twelve clinically healthy BaPedi goats with an average body weight of 19 ± 1.47 kg and an average age of 11±0.26 months were randomly selected from the flock at the University of Limpopo experimental farm. The experiment was conducted in three phases which are adaption, vaccination and moringa inclusion over 42 days. At the end of the first week of the trial, all the experimental goats were vaccinated with 2 millilitres of blanthrax vaccine per goat via the subcutaneous route. Three experimental diets were formulated by replacing a conventional supplement of Lucerne with M. oleifera. The inclusion levels varied from 0% to 50%. Data on the growth and haematological parameters of the animals used in the study were analysed using a general linear model (GLM) procedure in a completely randomized design. The results indicated that only platelet counts, monocyte counts and mean corpuscular volume (MCV) showed significant differences (p<0.05) amongst the 11 blood profiles observed in this study. There were significant differences (p<0.05) in body weight gain (BWG), growth rate (GR) and metabolic weight gain (MWG). No significant differences (p>0.05) were observed for feed intake (FI) and feed conversion ratio (FCR). Results of the present study suggest that M. oleifera leaves can be used as a feed supplement at 20% and 50% inclusion levels without having any adverse effects on blood parameters and growth performance.
Advances in Animal and Veterinary Sciences March 2022 | Volume 10 | Issue 3 | Page 573 - 581
Keywords: Dietary supplementation; Growth performance; Haematology; Natural forages; Vaccination; Hematology; Veterinary vaccines; Moringa oleifera; Buffelgrass; Goats